Human rights and drug control: access to controlled essential medicines in resource-constrained countries - Gispen, Marie Elske (School of Human Rights Research series, 2017)
"Globally, millions of people suffer health and socio-economic related problems due to the unavailability of controlled essential medicines, such as morphine for pain treatment, which leaves them in disabling and sometimes degrading situations. Controlled essential medicines are medicines included in the World Health Organization's List of Essential Medicines, and whose active substance is listed under the international drug-control treaties. Their availability and accessibility therefore fall within the remit of both human rights and international drug-control law. Even though the unavailability of controlled essential medicines is generally caused by a multifaceted and complex interplay of factors, the current international drug-control framework paradoxically hinders rather than fosters the access to medicines"--Back cover